Myrtenol Reduces Orofacial Nociception and Inflammation in Mice Through p38-MAPK and Cytokine Inhibition - Oliveira, Janaíne P.; Abreu, Fabíula F.; Bispo, José Marcos M.; Cerqueira, Anderson R. A.; Santos, José Ronaldo dos; Correa, Cristiane B.; Costa, Soraia K. P.; Camargo, Enilton A. (Frontiers in Pharmacology, 2022)
Orofacial pain is one of the commonest and most complex complaints in dentistry, greatly impairing life quality. Preclinical studies using monoterpenes have shown pharmacological potential to treat painful conditions, but the effects of myrtenol on orofacial pain and inflammation are scarce. The aim of this study was to evaluate the effect of myrtenol on experimental models of orofacial pain and inflammation. Orofacial nociceptive behavior and the immunoreactivity of the phosphorylated p38 (P-p38)-MAPK in trigeminal ganglia (TG) and spinal trigeminal subnucleus caudalis (STSC)were determined after the injection of formalin in the upper lip of of male Swiss mice pretreated with myrtenol (12.5 and 25 mg/kg, i.p.) or vehicle. Orofacial inflammation was induced by the injection of carrageenan (CGN) in the masseter muscle of mice pretreated with myrtenol (25 and 50 mg/kg, i.p.) or its vehicle (0.02% Tween 80 in saline). Myeloperoxidase (MPO) activity and histopathological changes in the masseter muscle and interleukin (IL)-1β levels in the TG and STSC were measured. The increase in face-rubbing behavior time induced by formalin and P-p38-MAPK immunostaining in trigeminal ganglia were significantly reduced by myrtenol treatment (12.5 and 25 mg/kg). Likewise, the increased MPO activity and marked inflammatory histological scores in masseter muscle, as well as the augmented levels of IL-1β in the TG AND STSC, observed after CGN injection were significantly decreased by myrtenol (25 and 50 mg/kg). Myrtenol has potential to treat orofacial inflammation and pain, which is partially related to IL-1β release in trigeminal structures and p38-MAPK modulation in trigeminal ganglia.